2009
DOI: 10.2190/pm.39.2.a
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Diabetes among Low-Income Hispanics: Design Elements of a Socio-Culturally Adapted Collaborative Care Model Randomized Controlled Trial

Abstract: Objective This article describes design elements of the Multifaceted Depression and Diabetes Program (MDDP) randomized clinical trial. The MDDP trial hypothesizes that a socioculturally adapted collaborative care depression management intervention will reduce depressive symptoms and improve patient adherence to diabetes self-care regimens, glycemic control, and quality-of-life. In addition, baseline data of 387 low-income, 96% Hispanic, enrolled patients with major depression and diabetes are examined to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 69 publications
3
91
0
Order By: Relevance
“…Although minority and low income patients may be at higher risk for depression, other studies have reported that these patient groups are significantly less likely to be screened and treated for depression [20,21,48]. Effective depression treatments are available [22,24,25,49,50], and the continuity of health care to optimally manage diabetes presents an opportunity to detect and treat depression in populations at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although minority and low income patients may be at higher risk for depression, other studies have reported that these patient groups are significantly less likely to be screened and treated for depression [20,21,48]. Effective depression treatments are available [22,24,25,49,50], and the continuity of health care to optimally manage diabetes presents an opportunity to detect and treat depression in populations at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to White Americans, Black and Hispanic Americans are more likely to experience persistent depressive symptom trajectories [6][7][8]. Thus, there is a need for ongoing enhanced socioenvironmental resources that support diabetes self-management, emotional well-being and glycemic control in this safety net population [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, decreasing the prevalence of depression in cancer patients significantly improves quality of life and cancer outcomes (10,12). Expanding methods to improve quality of life and clinical outcomes for patients with diabetes, which affects more than 285 million adults worldwide (26), is an additional step to preventing chronic disease progression.…”
Section: Discussionmentioning
confidence: 99%